Reducing properties, energy efficiency and carbohydrate metabolism in hyperhydric and normal carnation shoots cultured in vitro a hypoxia stress? - Saher, Shady (Plant physiology and biochemistry : PPB, 2005)
Hyperhydricity is considered as a physiological disorder that can be induced by different stressing conditions. In the present work we have studied the metabolic and energetic states of hyperhydric carnation shoots. We have evaluated the hypothesis that hypoxia stress is the main factor affecting the metabolism of hyperhydric leaves. Our results indicate a low level of ATP in hyperhydric tissues, but only slight modifications in pyridine nucleotide contents. Concurrently, the glucose-6-phosphate dehydrogenase (G-6-PDH; EC 1.1.1.49) activity in hyperhydric leaves was increased but glucokinase (GK; EC 2.7.1.2) activity was unchanged. We have observed that the metabolism of pyruvate was altered in hyperhydric tissues by the induction of pyruvate synthesis via NADP-dependent malic enzyme (EC 1.1.1.40). The enzymes of the fermentative metabolism pyruvate decarboxylase (PDC; EC 4.1.1.1) and alcohol dehydrogenase (ADH; EC 1.1.1.1) were highly increased in hyperhydric leaves. Sucrose metabolism was modified in hyperhydric leaves with a high increase in the activity of both synthesis and catabolic enzymes. The analysis of the sucrose, glucose and fructose contents indicated that all of these sugars were accumulated in hyperhydric leaves. However, the pinitol content was drastically decreased in hyperhydric leaves. We consider that these results suggest that hyperhydric leaves of carnation have adapted to hypoxia stress conditions by the induction of the oxidative pentose phosphate and fermentative pathways